Umbilical cord-derived mesenchymal stem cells alleviate liver fibrosis in rats - Chai, Ning-Li (World J Gastroenterol, 2016)
AIM: To evaluate the efficacy of umbilical cord-derived mesenchymal stem cells (UC-MSCs) transplantation in the treatment of liver fibrosis. METHODS: Cultured human UC-MSCs were isolated and transfused into rats with liver fibrosis induced by dimethylnitrosamine (DMN). The effects of UC-MSCs transfusion on liver fibrosis were then evaluated by histopathology; serum interleukin (IL)-4 and IL-10 levels were also measured. Furthermore, Kupffer cells (KCs) in fibrotic livers were isolated and cultured to analyze their phenotype. Moreover, UC-MSCs were co-cultured with KCs in vitro to assess the effects of UC-MSCs on KCs’ phenotype, and IL-4 and IL-10 levels were measured in cell culture supernatants. Finally, UC-MSCs and KCs were cultured in the presence of IL-4 antibodies to block the effects of this cytokine, followed by phenotypical analysis of KCs. RESULTS: UC-MSCs transfused into rats were recruited by the injured liver and alleviated liver fibrosis, increasing serum IL-4 and IL-10 levels. Interestingly, UC-MSCs promoted mobilization of KCs not only in fibrotic livers, but also in vitro. Co-culture of UC-MSCs with KCs resulted in increased production of IL-4 and IL-10. The addition of IL-4 antibodies into the co-culture system resulted in decreased KC mobilization. CONCLUSION: UC-MSCs could increase IL-4 and promote mobilization of KCs both in vitro and in vivo, subsequently alleviating the liver fibrosis induced by DMN.